Improving the accuracy of energy yield calculations of tandem solar cell‐based CPV‐modules. (29th September 2021) - Steiner, Marc; Mathur, Paresh; Sarkar, Subrata; Siefer, Gerald
Abstract: Energy yield calculations for CPV modules that use tandem solar cell technology have been performed and analysed in this work. Two BSQ D280 CPV modules were used as specimen: one located in Freiburg, Germany, and one in Greater Noida, India. The current–voltage curves of both modules were measured for several months together with the prevailing ambient conditions. The energy yield in the respective measurement periods were calculated using the software PVsyst. It has been found that the energy yield modelled with PVsyst has a good agreement with the one measured in Freiburg, but deviates by 10% from the one measured in Greater Noida. The reason is most likely the high aerosol content in Greater Noida and thus the non‐appropriate consideration of spectral irradiance impact by PVsyst, which uses air mass and DNI as the only atmospherical parameters. The accuracy of the PVsyst calculation has been strongly improved in this work by using SMR corrected DNI values as input for the PVsyst calculation. In this manner, the impact of spectral irradiance variation on (C)PV module power output can be considered in energy yield calculations by PVsyst. The deviation of the calculated and measured energy yield could be reduced to below 1%. Abstract : Energy yield calculations for CPV modules that use tandem solar cell technology have been performed and analysed in this work. It has been found that the energy yield modelled with PVsyst has a good agreement with the one measured in Germany, but deviates by 10% from the one measured in India. The accuracy of the PVsyst calculation in India has been strongly improved in this work (below 1%) by using SMR corrected DNI values as input for the PVsyst calculation.